Modeling Anxiety Sensitivity Based on Early Maladaptive Schemas and Cognitive Emotion Regulation Strategies with the Mediating Role of Parenting Styles - Aman Alah Khani Ghashghaee, Sara; Javidi, Hojatollah; Baghooli, Hossein (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2024)
Objective: Although most young individuals transition from adolescence successfully and without encountering significant issues, there can be challenges and obstacles during this period that prevent the full utilization of one’s abilities and potential. The present study aimed to model anxiety sensitivity based on early maladaptive schemas and cognitive emotion regulation strategies with the mediating role of parenting styles. Methods and Materials: This research is of a correlational type. The sample included 100 mothers of first-grade students from the city of Shiraz during the 2018-2019 academic year, selected through multi-stage cluster sampling. The sample size, based on Kline’s (2010) criterion, was determined by selecting five individuals per item, resulting in a selection of 570 participants. Data were collected using the Taylor and Cox Revised Anxiety Sensitivity Index, the short form of Young’s Early Maladaptive Schemas Questionnaire, the Garnefski and Kraaij Cognitive Emotion Regulation Questionnaire, and Diana Baumrind’s Parenting Styles Questionnaire. To obtain preliminary information on the measured variables, statistical indices such as mean and standard deviation, as well as the correlation matrix of the variables, were calculated. SPSS and Amos software were used to analyze the data and examine the proposed research model. Findings: The results of the study indicated that parenting styles played a mediating role in the relationship between exogenous variables (maladaptive schemas, maladaptive emotion regulation strategies, and adaptive emotion regulation strategies) and anxiety sensitivity. Conclusion: Given the impact of maladaptive schemas on psychological disorders, it is recommended that schema therapy workshops be held for all patients suffering from depression and anxiety.